HUBUNGAN PENGETAHUAN, SIKAP DAN PAPARAN MEDIA INFORMASI DENGAN PRAKTIK PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA SANTRIWATI PONDOK PESANTREN AL ISHLAH TEMBALANG SEMARANG TAHUN 2016 - Dinnia Hanivah Novasari; Djoko Nugroho; Sri Winarni (Jurnal Kesehatan Masyarakat (Undip), 2016)
Breast self-examination (BSE) is one way in early detection which aims to determine the existence of a mass in the breast. But in reality, awareness to practice BSE is still lacking especially in young women (25%-30%). Based on a preliminary study of 10 female students, 90% students do not know about the practice of breast self-examination (BSE). This study aimed to analyze the correlation between knowledge, attitudes and practices of media exposure information with breast self-examination (BSE) on santriwati Pondok Pesantren Al Islah Tembalang Semarang. This type of research is explanatory research with cross sectional study. The population are all female students of Pondok Pesantren Al Islah sample is 40. Analysis of the data used univariate, bivariate descriptive analysis, and analytic bivariate analysis using statistical test of Rank Spearman. Value significance relationships using a significance value (α = 5%). The results showed the largest percentage of female students on the knowledge contained less (82.5%), enough attitude (65%) and exposure to the media information that are not exposed (52.5%). Lack of knowledge about the practice (84.8%), good knowledge with enough practice (75%), sufficient knowledge with good practices (33.3%), good attitude with less practice (100%), less attitude with good practice (30%), enough attitude with good practice (3.8%), not exposed to media with less practice (90.5%), enough exposure with enough practice (66.7%), less exposure with good practice (33.3%). The results of Spearman Rank analysis showed that there is correlation between knowledge (p value = 0.001; r = 0.599; 95% CI = 0.263 to 0.852), the media exposure information with BSE practice (p value = 0.001; r = 0.507; 95% CI = 0.211 to 0.730) the practice of BSE, there is no correlation with attitude (p-value 0.489; r = 0.113; 95% CI = -0,151-0,852) with BSE practice. It suggested to cooperate with Bapermas to giving information and add a study on the practice of Breast Self Examination (BSE) in science subject every week.